First record of hygropetric species in the genus Paegniodes Eaton, 1881 (Ephemeroptera: Heptageniidae) with description of a new species from China - Shi, Weifang; Tong, Xiaoli (Zootaxa, 2023)
Paegniodes oligopilus sp. nov., a first hygropetric species in the genus Paegniodes Eaton, 1881 found from madicolous habitat, is described based on larvae from Southwest China. The new species is characterized by the posterior margin of 1st segment bearing a row of 13–15 stout setae; mesonotum and abdominal tergites II–IX having a reddish brown median stripe; swimming setae of cerci and median caudal filament are vestigial. The morphological affinities and feeding habits with other known species are discussed.